2015
DOI: 10.1097/icl.0000000000000083
|View full text |Cite
|
Sign up to set email alerts
|

Scleral Lenses

Abstract: Indications for scleral lens wear are well-established. Developing areas of research on the physiologic impact of scleral lens wear on the ocular surface, the use of technology to improve scleral lens vision and fit, and the impact of these devices on the quality of life should further enhance our understanding of scleral lenses in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(43 citation statements)
references
References 139 publications
0
37
0
1
Order By: Relevance
“… 22 The overall success rate of scleral family lenses has been reported 70–80% in the literature review variable in different indications. 8 Their highly gas permeable material makes them a good option for correcting aphakia since they are required to be used for longer hours in this situation. As the MSD lenses are smaller and less expensive than scleral lenses, and they might be easier to fit, they can be better choices when compared to other lenses of the scleral family in patients with ocular surface abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“… 22 The overall success rate of scleral family lenses has been reported 70–80% in the literature review variable in different indications. 8 Their highly gas permeable material makes them a good option for correcting aphakia since they are required to be used for longer hours in this situation. As the MSD lenses are smaller and less expensive than scleral lenses, and they might be easier to fit, they can be better choices when compared to other lenses of the scleral family in patients with ocular surface abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“… 2 , 10 In a literature review of scleral lenses, Schornack et al 70 reported two incidence rates, between 0.5 and 1.6%, 28 of microbial or Acanthamoeba keratitis among post-surgical eyes or those with severe ocular surface disease, which are known risk factors for infection. 71 Zimmerman and Marks 54 reported on a case of microbial keratitis associated with poor compliance with scleral lens use in a case of neurotrophic keratitis. Walker et al 2 reviewed 11 cases of microbial keratitis from the literature, all of which either were post-surgical eyes or had pre-existing epithelial defects.…”
Section: Discussionmentioning
confidence: 99%
“…They have recently gained more interest among practitioners around the world and are one of the first and best visual correction options for eyes that are unsuccessful with conventional contact lens modalities. Evolutions in lens materials, production techniques and improved knowledge on anterior ocular surface anatomy, boosted the indications of scleral lens fitting, varying from severely irregular corneas to normal/ healthy corneas [1][2][3].…”
Section: Introductionmentioning
confidence: 99%